ALTERNATIVE ORGANIC SUBSTRATES FOR THE INITIAL DEVELOPMENT OF Passiflora edulis f. flavicarpa Deg. SEEDLINGS (REMUNOM, 2026)
The present research aimed to evaluate which better concentration of substrates promotes greater initial development of seedlings of Passiflora edulis f. flavicarpa Deg. The experiment was conducted in the vegetation house of the Tabuleiro Costeiro Embrapa Unit, located on the Campus de Engenharias e Ciências Agrárias – CECA/UFAL, Rio Largo-AL, where seven treatments were tested: T0 – 100% soil (control); T1 - soil + 10% sheep manure; T2 – soil + 20% sheep manure; T3 – soil + 33% sheep manure; T4 – soil + 10% coffee grounds; T5 – soil + 20% coffee grounds; T6 – soil + 33% coffee grounds, with five repetitions, totaling 35 polyethylene bags with a volume of three liters. The evaluated parameters were: number of leaves (NF), height (H), leaf area (AF), stem diameter (DC), root length (CR), leaf dry matter content (TMSF), stem (TMSC), root (TMSR) and total dry matter content (TMST). Contrary to expectations, seedlings produced with coffee grounds did not show gains in initial development. Regarding the substrate containing sheep manure, it was observed that its use in concentrations of 33% can impair its decomposition and consequently the availability of nutrients for the plants. The substrate containing coffee grounds proved to be unfeasible and that its use "in natura" acidifies the soil and should be better studied. Thus, it is recommended for the production of Passiflora edulis f. flavicarpa Deg. the use of sheep manure substrate at a concentration of 20%.